The effect of psychiatric comorbidities and stress-coping strategies on perceived quality of life in migraine - Petrovics-Balog, Anna; Majláth, Zsófia; Melinda, Lukács; Holczer, Adrienn; Must, Anita; Tajti, János; Vécsei, László (Ideggyógyászati szemle, 2019)
Migraine is one of the most disabling primary headache conditions. We aimed to detect hidden symptoms of anxiety and depression and to survey stress-coping mechanisms and related quality of life in a large migraine population without any known psychiatric comorbidity. 123 migraine patients (MG) and 66 healthy subjects (HC) completed the Beck Depression Inventory-II (BDI-II), the State and Trait Anxiety Inventory (S-STAI and T-STAI), the Stress and Coping Inventory (SCI) and the 36-Item Short Form Health Survey (SF-36). MG patients reached significantly higher scores on the BDI-II and the T-STAI yielding previously undetected anxiety and depression symptoms. Significant differences were present on the SCI: higher stress scores and lower coping levels suggested impaired stress-coping strategies in migraine. MG patients achieved significantly lower scores on most of SF-36 subscales indicating lower perceived quality of life. Significant correlations were found between BDI-II, T-STAI, SCI scores and subscales of the SF-36. Unrecognized symptoms of anxiety and depression, as well as less effective stress-coping strategies might be related to the lower perceived quality of life in migraine. The screening of these symptoms might lead to more focused and efficient therapeutic strategies. Addressing stress management techniques could improve quality of life on the long-term.